The framework of urban exposome: application of the exposome concept in urban health studies - Andrianou, Xanthi; Makris, Konstantinos C. (My University, 2018)
Horizontal challenges, such as climate change or the growing populations, and their manifestations require the development of multidisciplinary research synergies in urban health that could benefit from concepts, such as the human exposome. Cities are composed of interconnected systems which are influenced, by global trends, national policies and local complexities. In this context, the exposome concept could be expanded having the city setting in its core, providing the conceptual framework for the new generation of urban studies. The objectives of this work were to define the urban exposome and outline its utility. The urban exposome can be defined as the continuous spatiotemporal surveillance/monitoring of quantitative and qualitative indicators associated with the urban external and internal domains that shape up the quality of life and the health of urban populations, using small city areas, i.e. neighborhoods, quarters, or smaller administrative districts, as the point of reference. Research should focus on the urban exposome's measurable units at different levels, i.e. the individuals, small, within-city areas and the populations. The urban exposome framework applied in the city of Limassol, Cyprus combines three elements: (i) a mixed-methods study on stakeholders' opinions about quality of life in the city; (ii) a systematic assessment of secondary data from the cancer and death registries, including city infrastructure data; and (iii) a population health and biomonitoring survey. Continuous assessment of environmental and health indicators that are routinely collected, and the incorporation of primary data from population studies, will allow for the timely identification of within-city health and environmental disparities to inform policy making and public health interventions. The urban exposome could facilitate evidence-based public health response, offering researchers, policy-makers, and citizens effective tools to address the societal needs of large urban centers.
Keywords: Exposome; Urban health; Environment; Disparities; Climate change; Metabolomics; Cities; Monitoring; Spatiotemporal; Indicators